A General Method to Develop Highly Environmentally Sensitive Fluorescent Probes and AIEgens. Issue 5 (19th December 2021) - Miao, Rong; Li, Jing; Wang, Chao; Jiang, Xuefeng; Gao, Ying; Liu, Xiaoling; Wang, Dan; Li, Xin; Liu, Xiaogang; Fang, Yu
Abstract: Environmentally sensitive fluorescent probes (including AIEgens) play pivotal roles in numerous biological studies. Many of these functional materials are developed based on the twisted intramolecular charge transfer (TICT) mechanism. However, the TICT tendency of dialkylated amino groups in biocompatible main‐stream fluorophores (i.e., coumarins and rhodamines) is weak, limiting their sensitivities. Herein, by replacing dialkylated amino donors with an N ‐methylpyrrole group to enhance TICT, a simple and general method to engineer highly environmentally sensitive fluorescent probes is reported. This method yields a platter of colorful fluorescent probes that demonstrates outstanding polarity and viscosity sensitivity with large turn‐on ratios (up to 191 times for polarity and 14 times for viscosity), as well as distinct aggregation‐induced emission (AIE) characteristics. The utilities of these probes in both wash‐free bioimaging and protein detections are also successfully demonstrated. It is expected that this molecular design strategy will inspire the creation of many environmentally sensitive probes. Abstract : Replacing a dialkylated amino donor with an N ‐methylpyrrole group effectively enhances twisted intramolecular charge transfer (TICT) tendency in biocompatible main‐stream fluorophores. This simple and general method leads to a series of probes with greatly enhanced environmental sensitivity for biological applications and AIEgen development.